Information Services Using Problem Based Learning to Prevent Online Game Addiction - Fachriza Rahmi; Neviyarni Neviyarni; Mega Iswari (Jurnal Neo Konseling, 2022)
This study aims to (1) analyze the level of understanding of the dangers of online game addiction of the experimental group students before (pretest) and after (posttest) given information services with a problem based learning model, (2) analyze the level of understanding of the dangers of online game addiction of control group students before ( pretest) and after (posttest) given information services, (3) testing the effectiveness of information services using a problem based learning model to prevent online game addiction. This study uses a quasi-experimental quantitative method of non-equivalent control group design. The research sample was class XI SMAN 13 Padang as many as 15 students in the experimental group and 15 students in the control group. The sample used was purposive sampling. Statistical analysis used is descriptive analysis and non-parametric statistics. The results showed that (1) there was an increase in the understanding of the dangers of online game addiction by the experimental group students before and after being given information services using a problem based learning model, (2) there was an increase in the understanding of the dangers of online game addiction by the control group students before and after being provided with information services, ( 3) there is a significant difference in the level of understanding of the dangers of online game addiction by the experimental group students who were provided with information services using a problem based learning model with the control group which was only provided with information services. Thus, information services using a problembased learning model are more effective in preventing students' online game addiction.